2009
DOI: 10.3340/jkns.2009.46.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Change of Lumbar Motion after Multi-Level Posterior Dynamic Stabilization with Bioflex System : 1 Year Follow Up

Abstract: Objective : This study examined the change of range of motion (ROM) at the segments within the dynamic posterior stabilization, segments above and below the system, the clinical course and analyzed the factors influencing them. Methods : This study included a consecutive 27 patients who underwent one-level to three-level dynamic stabilization with Bioflex system at our institute. All of these patients with degenerative disc disease underwent decompressive laminectomy with/without discectomy and dynamic stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
4
7
0
5
Order By: Relevance
“…These two factors can explain the reduced preoperative LL (-20.90 ο ±1.92 ο ) which was further reduced at 3 months (-17.05 ο ±1.88 ο ) and remained almost stable at 6 months (-18.95 ο ±2.26 ο ). The course of the initial reduction and then the increase in the lordosis is also reported by other researchers who examined the posterior lumbar fusion [ 33 ]. However, the fact that the LL was just -21.40 ο ±1.98 ο even at 12 months postoperatively, is the result of the use of a stabilization system with rods in the applied-technique [ 4 , 33 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These two factors can explain the reduced preoperative LL (-20.90 ο ±1.92 ο ) which was further reduced at 3 months (-17.05 ο ±1.88 ο ) and remained almost stable at 6 months (-18.95 ο ±2.26 ο ). The course of the initial reduction and then the increase in the lordosis is also reported by other researchers who examined the posterior lumbar fusion [ 33 ]. However, the fact that the LL was just -21.40 ο ±1.98 ο even at 12 months postoperatively, is the result of the use of a stabilization system with rods in the applied-technique [ 4 , 33 ].…”
Section: Discussionsupporting
confidence: 61%
“…The course of the initial reduction and then the increase in the lordosis is also reported by other researchers who examined the posterior lumbar fusion [ 33 ]. However, the fact that the LL was just -21.40 ο ±1.98 ο even at 12 months postoperatively, is the result of the use of a stabilization system with rods in the applied-technique [ 4 , 33 ]. Characteristically, Boos and Webb (1997) [ 4 ] reported that the use of rods reduces the LL especially if the fusion includes healthy motion segments.…”
Section: Discussionsupporting
confidence: 61%
“…Cakir et al reported adjacent level disc pressure and adjacent level facet joint pressure as other factors contributing to the risk of ASD after fusion of the lumbar spine (2). Park et al suggested putative risk factors associated with ASD in lumbar or lumbosacral fusion groups, such as facet violation, fusion length, pre-existing degenerated disc at the adjacent level, lumbar stenosis, age, osteoporosis, and post-menopausal state (15). We suggest that risk factors of additional stress on adjacent segments after fusion surgery were related to possible multiple conditions, and not only to fusion device difference as stated in previous reports.…”
Section: █ Discussionsupporting
confidence: 58%
“…Among these complications, acceleration of ASD is common and can lead to significant stenotic lesion, instability, and disc rupture, requiring an additional surgical modality. It has been proposed that lumbar fusion surgery may induce hyper-mobility with increasing intradiscal pressure at adjacent segments and alterations in axial loading distribution (15).…”
Section: █ Acknowledgementmentioning
confidence: 99%
“…4,15 Some reports have demonstrated good clinical outcomes and a preventive effect on adjacent level degeneration of the BioFlex dynamic stabilization system. 4,15 Some reports have demonstrated good clinical outcomes and a preventive effect on adjacent level degeneration of the BioFlex dynamic stabilization system.…”
Section: Discussionmentioning
confidence: 99%